Research on Knee Joint Load and Influencing Factors of Typical Tai Chi Movements - Cenyi Wang; Ganfeng Yang; Haoping Yang; Changde Chen; Henrui Zhang; Kailong Wang; Aming Lu (Applied Bionics and Biomechanics)
Background. Tai chi is recognized worldwide for its rehabilitation abilities and healthcare benefits. However, in recent years, some movements associated with tai chi have been shown to damage the lower limb joints. The purpose of this study was to investigate and compare the effects of different movements, postures, center of mass (COM) movements, and range of knee movement of tai chi exercises on knee joint load. Methods. Fourteen professional tai chi practitioners in two postures (high and low) were enrolled to perform the following four typical tai chi movements: wild horse’s mane (WHM), repulse monkey (RM), wave-hand in cloud (WHIC), and grasp the bird’s tail (GBT). Kinematic and kinetics data were synchronously collected using the Vicon infrared high-speed motion capture system and a three-dimensional (3D) force measurement platform. Variance analysis and partial correlation analysis were performed to investigate factors influencing peak knee joint moment and vertical ground reaction force (VGRF). Results. The results showed that the peak knee extension and abduction moment were larger in WHM and RM than those in WHIC and GBT (p<0.05). WHM was associated with greater rotation moment than the other typical movements (p<0.05). VGRF and joint moment among different poses were significantly different. Low-pose tai chi typical movements were associated with greater VGRF, knee joint extension and abduction, and rotation moments than high-pose movements (p<0.05). The anteroposterior and mediolateral COM displacements were strongly and positively associated with VGRF (p<0.001), while the mediolateral COM displacement was negatively associated with knee extension moment (p<0.001). The knee internal-external rotation ROM and anteroposterior and mediolateral COM displacements were positively associated with knee abduction moment (p<0.01). Conclusion. For long-term tai chi exercises, choosing a suitable posture based on an individual exercise level and reasonable control of knee ROM and COM displacement can reduce the risk of knee injury during exercise.